Case Report: CASPR2-associated autoimmune encephalitis with NF155 Antibody-positive autoimmune nodopathies: a rare case with hyponatremia onset - Wen-Ya Wang; Wen-Ya Wang; Wen-Ya Wang; Jing-Ying Huang; Jing-Ying Huang; Jing-Ying Huang; Ying Xue; Ying Xue; Ying Xue; An-Ran Zhang; An-Ran Zhang; An-Ran Zhang; et al. (Frontiers in Immunology)
ObjectivesThis case report aims to highlight the atypical presentation and management of a patient diagnosed with CASPR2-associated autoimmune encephalitis and NF155 antibody-positive autoimmune nodopathies (AN), initially presenting with limb weakness and hyponatremia.MethodsThe patient was identified through clinical evaluation and diagnostic testing including serum and cerebrospinal fluid analysis, neuroimaging, and nerve conduction studies.ResultsThe patient exhibited limb weakness, hyponatremia, cognitive abnormalities, and peripheral nerve involvement. Diagnostic testing revealed CASPR2 and NF155 antibody are positive. Therapeutic interventions included corticosteroids, plasma exchange, and intravenous immunoglobulin therapy, followed by B-cell depletion therapy. Treatment led to improvement in walking function and normalization of antibodies.DiscussionThis case report contributes to the literature by documenting a rare co-occurrence of CASPR2-associated autoimmune encephalitis and NF155 antibody-positive AN, with a unique presentation of hyponatremia. The findings underscore the importance of considering autoimmune etiologies in patients presenting with hyponatremia and neurological symptoms. Moreover, the favorable response to B-cell depletion therapy suggests a potential treatment option for similar cases. The main take away is the need for heightened clinical suspicion and comprehensive diagnostic evaluation in patients with complex neurological presentations, to facilitate timely diagnosis and appropriate management.